Effects of garlic extract on TNF-α expression and oxidative stress status in the kidneys of rats with STZ + nicotinamide-induced diabetes - Nasrin Ziamajidi; Abolfazl Nasiri; Roghayeh Abbasalipourkabir; Somayeh Sadeghi Moheb (Taylor & Francis Group, 2017)
Context: Allium sativum L. (Liliaceae) (garlic) is a medicinal plant that is widely used in herbal medicine. Nephropathy is a complication of diabetes that is induced by long-term hyperglycaemia. Objective: The effects of aqueous extract of garlic (AGE) on the expression of tumour necrosis factor-alpha (TNF-α) and oxidative stress status were studied in the kidneys of rats with streptozotocin (STZ) + nicotinamide-induced diabetes. Materials and methods: Twenty-four Wistar rats were divided into four groups: control rats, rats with STZ + nicotinamide-induced diabetes that received a single dose of STZ (65 mg/kg) and nicotinamide (110 mg/kg) intraperitoneally, diabetic rats that were treated with garlic (2 g/kg/d, gavage), and normal rats that received garlic (2 g/kg/d, gavage). The glucose level was determined in the start of study, 7 d after induction of diabetes and 33 d after treatment with garlic. At the end of the treatment period, urea, uric acid and creatinine levels were estimated in sera. Malondialdehyde (MDA), total oxidant status (TOS), nitric oxide (NO) levels and TNF-α gene and protein expression were measured in the renal tissues of the rats. Results: The glucose, uric acid, and urea levels increased in the serum of diabetic rats compared with control rats, and decreased in garlic-treated diabetic rats compared with diabetic rats (p < 0.05). MDA, TOS and NO increased (p < 0.001) in diabetic rats compared with the control group, and decreased in garlic-treated diabetic rats compared with diabetic rats (p < 0.01). The level of TNF-α mRNA did not differ between groups but the TNF-α protein level in diabetic rats was higher than in the control rats (p < 0.01), whereas after treatment with garlic, it was close to the normal level (p < 0.01). Discussion and conclusion: These results indicate that garlic extract has hypoglycaemic, antioxidant and anti-inflammatory properties; therefore, it can be useful for the alleviation of diabetic complications.